(untitled) (Research, Society and Development, 2023)
Introduction: Health literacy (HL) is considered a factor that interferes with warfarin treatment, since the literature indicates an association between low understanding of the treatment and inadequate control of oral anticoagulation. The study aimed to characterize patients with low functional health literacy in an anticoagulation clinic in Minas Gerais. Methodology: The work was carried out at the anticoagulation outpatient clinic at the UFMG clinic hospital. Participants signed the consent form, respecting the precepts of bioethics. Individuals with inadequate TTR values (TTR <60%) and low functional health literacy were included. Numerical variables were described taking into account the mean and standard deviation and categorical variables according to percentile distribution. Results: The study presents elderly females residing in Belo Horizonte and the metropolitan region as the majority population. Participants had an average study time of 3.9 years and 19.6% of those involved reported not knowing how to read. Still, 37.3% reported that they had had a stroke prior to hospitalization and 19.6% had Chagas cardiomyopathy. Polypharmacy was detected in 84.3% of the participants, 58.8% had a high complexity of pharmacotherapy and the average number of medications in continuous use was 6.5. Conclusion: The data obtained in this study reinforce the fragility of patients with low health literacy, leading to the need to implement care and follow-up strategies for these patients in search of equity in health care.